Keterbukaan Informasi Pelaku Usaha Dalam Perjanjian Jual Beli Apartemen Secara Pre Project Selling; Analisis Putusan No.224/Pdt.G/2017/Pn.Jkt.Sel - Dewi Rara Pertiwi; Fitriyani Zein (JOURNAL of LEGAL RESEARCH, 2019)
AbstractIn apartment selling, there are developers who are not open and transparent about the given information on marketing and selling with pre project selling system. There are also unclear informations about agreement between business actor and consumer that written in Sale and Purchase Agreement (PPJB) which given by developer. This case is certainly contrast to Pasal 7 Undang-undang Nomor 8 Tahun 1999 about Consumer Protection. In fact, pre project selling system often places consumers into weak situation and prone to default act by business actors. According to the researcher, the result from judge’s council is fair enough and appropriate according to existing regulation, but Law Number 20 of 2011 concerning Flats still ineffective because it had not implement regulation act of the law.Keywords: Information Disclosure, Sale and Purchase Agreement, Apartment, and Pre Project Selling